1967
DOI: 10.1001/archpedi.1967.02090180124012
|View full text |Cite
|
Sign up to set email alerts
|

Shock as a Complication of the Nephrotic Syndrome

Abstract: THE occurrence of shock has been reported as a rare complication of the nephrotic syndrome. A number of reports have demonstrated the association of hypovolemia with shock in the nephrotic state.1-5 Farr described recurrent "nephrotic crises" usually associated with infection and hypoaminoacidemia. Although plasma volumes were not estimated and hypotension was not reported, four out of five children reported had high venous hematocrit determinations during the crisis. 6 The present report describes the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1967
1967
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A reduction in plasma volume is the most common explanation of the reduced GFR (14,16). Although hypovolaemia may occur in the nephrotic syndrome (17,18), it has recently been shown that this is usually not the case (2,19). Nor is the reduced GFR accompanied by a corresponding reduction in the renal plasma flow (2, 3) but instead, a low FF has been reported (2, 3) and has been suggested to be caused by a reduced glomerular permeability to water (3).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in plasma volume is the most common explanation of the reduced GFR (14,16). Although hypovolaemia may occur in the nephrotic syndrome (17,18), it has recently been shown that this is usually not the case (2,19). Nor is the reduced GFR accompanied by a corresponding reduction in the renal plasma flow (2, 3) but instead, a low FF has been reported (2, 3) and has been suggested to be caused by a reduced glomerular permeability to water (3).…”
Section: Discussionmentioning
confidence: 99%
“…Patients, usually children, with the nephrotic syndrome who are in remission occasionally have a relapse, with profound proteinuria and loss of albumin in urine and into ISF sufficient to cause shock. The loss may reduce PV by half and plasma albumin even more [38,39]. While the first impulse is to give albumin as HSA, giving only Ringer's solution may be better.…”
Section: Isf Support When Pv Is Compromisedmentioning
confidence: 99%
“…In pediatric practice, the primary type appears more frequently than the secondary type. The ratio of primary to secondary type has been reported as 3:7 (Yamauchi and Hopper, 1964) but there are many reports which show all are primary type (Reimold et al 1966;Egan et al 1967;Tagawa et al 1973;Okamura et al 1982; and this study).…”
Section: Discussionmentioning
confidence: 51%
“…It had then been speculated that the cause of nephrotic crisis (Cx) was an infection such as pneumococcic bacteriemia or penitonitis. Other causes have been suggested, (Yama chi and Hopper, 1964) More recently there have been many pediatric reports of spontaneous Cx, where hypovolemic shock has been proposed as a main factor in the cause although there was little evidence reported and the role of hypoadrenocorticism was ignored, (Reimold et al 1966;Egan et al 1967;Nonoda et al 1973;Tagawa et al 1973 andOkamura et al 1982).…”
Section: Introductionmentioning
confidence: 99%